Recent Advances in Doxorubicin Formulation to Enhance Pharmacokinetics and Tumor Targeting - Jihoon Lee; Min-Koo Choi; Im-Sook Song (MDPI AG, 2023)
Doxorubicin (DOX), a widely used drug in cancer chemotherapy, induces cell death via multiple intracellular interactions, generating reactive oxygen species and DNA-adducted configurations that induce apoptosis, topoisomerase II inhibition, and histone eviction. Despite its wide therapeutic efficacy in solid tumors, DOX often induces drug resistance and cardiotoxicity. It shows limited intestinal absorption because of low paracellular permeability and P-glycoprotein (P-gp)-mediated efflux. We reviewed various parenteral DOX formulations, such as liposomes, polymeric micelles, polymeric nanoparticles, and polymer-drug conjugates, under clinical use or trials to increase its therapeutic efficacy. To improve the bioavailability of DOX in intravenous and oral cancer treatment, studies have proposed a pH- or redox-sensitive and receptor-targeted system for overcoming DOX resistance and increasing therapeutic efficacy without causing DOX-induced toxicity. Multifunctional formulations of DOX with mucoadhesiveness and increased intestinal permeability through tight-junction modulation and P-gp inhibition have also been used as orally bioavailable DOX in the preclinical stage. The increasing trends of developing oral formulations from intravenous formulations, the application of mucoadhesive technology, permeation-enhancing technology, and pharmacokinetic modulation with functional excipients might facilitate the further development of oral DOX.